Downstreaming nanoemulsion-based botanical insecticides: Enhancing competitiveness and sustainability of organic horticulture for KWT Kayu Gadang - Tama, Duma Putri; Erona, Meisilva; Oktavia, Fitriyeni; Lina, Eka Candra (Community Empowerment, 2025)
Dependency on chemical pesticides is a major hurdle in achieving competitive and safe organic horticultural cultivation. This community service program aims to implement nanoemulsion-based botanical insecticide innovation as an eco-friendly pest control solution for the Kayu Gadang Women Farmer Group (KWT) in Sawahlunto. The methodology employed a participatory approach involving technology transfer, digital financial management mentoring, and product branding strategies. Evaluation results demonstrated significant impacts across three key pillars: an 80% reduction in chemical pesticide use per planting season, improved quality of residue-free horticultural products, and a 25% increase in business turnover. Additionally, marketing effectiveness rose, with sales volume growing by 50%. This program successfully transformed KWT Kayu Gadang into a self-sufficient and competitive horticultural business unit that supports green technology-based sustainable agriculture.